POSSIBLE GEOCHEMICAL CONDITIONS OF LOCAL REDUCING ENVIRONMENTS IN THE EARTH'S CRUST AND UPPER MANTLE - Yaroshevskii A.A. (My University, 2006)
The proportion of ç2é + ç2 in the gas phase equilibrated with an assemblage of solid phases is buffered by the interaction with Fe and is related to the ratios of FeO (Fe) and Fe3O4 (FeO) activities in the solid phases at a given temperature. In a closed system, the proportion of Fe and H is set by the relative amounts of Fe, O, and H. If the amount of Fe compounds substantially exceeds the equivalent mass of hydrogen compounds, the degree of Fe oxidation, i.e., the FeO/Fe3O4 or Fe/FeO ratios, uniquely controls the ratio of H2 and ç2é in the gas phase.